LINEARITY IN LANGUAGE. RHETORICAL-DISCURSIVE PREFERENCES IN ENGLISH AND SPANISH IN THE LIGHT OF KAPLAN’S MODEL - Monroy Casas, Rafael (International Journal of English Studies, 2008)
In the present work the author tries to analyse one of the fundamental concepts that underlie Kaplan’s theory: his idea of “linearity”. Rather surprisingly, despite its importance, it is a construct that usually goes undefined in the literature. Different parameters of rhetorical organisation will be considered in this paper in order to clarify the essence of linearity. We shall check then Kaplan’s contention that English is a “linear” language whereas Spanish, a member of the Romance family, is characterised by a broken or non-linear structure. We shall also verify if there exist differences between English and Spanish in the discursive organisation of an expository text. Finally, we shall discuss which parameters appear to be more coincidental and more divergent within the rhetorical organisation of each language.